Implementation of Digital Transactions for MSMEs Business Actors in South Kembangan Village - Kurniawati , Elok; Sormin, Feber (MOVE: Journal of Community Service and Engagement, 2025)
(1) Micro, small, and medium enterprises are one of the drivers of the economy in Indonesia, this is what encourages the government to create regulations for MSMEs (2) A digital transaction platform is a system or application that facilitates various types of financial transactions electronically, including payments and fund transfers, through digital devices such as computers or mobile phones. Examples are digital wallets (e-wallets), mobile banking, and payment gateways (3) Digital transactions can be done anywhere, anytime and provide a sense of security and comfort for MSMEs as well as an efficient and effective way to avoid counterfeit money (4) It is hoped that the training provided through community service in South Kembangan Village can motivate the community to use technology wisely and MSMEs can become pillars in the national economy.